ANALISIS PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS VISUAL DALAM MENINGKATKAN KEAKTIFAN BELAJAR PESERTA DIDIK - Christina Mety; Bambang Budi Utomo; Thommy Sastrawan Atmaja (Universitas Tanjungpura, 2020)
Abstract This study aims to describe the planning, implementation, and assessment of student's activeness on PPKn subjects in class X Science of Abdi Wacana Christian High School Pontianak using visual based learning media . This type of research is qualitative with descriptive methods. The research subjects consist of 19 students of class X Science. The data collection techniques are observation, interviews and documentation. Based on the results of the study found that: 1. On the teacher's Lesson Plan is in accordance with the components and systematic K-13 Lesson Plan and the preparation of the Lesson Plan has designed learning activities that can develop student learning activities. 2. The implementation of learning at the first and second meetings, the teacher has implemented according to the Lesson Plan using visual-based media. 3. The student learning activeness from the first and second meetings on average students are very active by meeting 5 indicators of activeness. Therefore, it can be concluded that visual based learning media can develop the learning activeness of students on PPKn subjects in class X Science of Abdi Wacana Pontianak Christian High School. Keywords: Learning Activness, PPKn, Visual Media